Pengaruh Sektor Industri, Sektor Pertanian, Dan Sumber Daya Manusia Terhadap Ketimpangan Pembangunan Di Jawa Barat Tahun 2015-2019 - Ria Nurul Azizah; Atik Mar’atis Suhartini (Seminar Nasional Official Statistics, 2021)
West Java is province having high contribution on Indonesian economy. However, Inequality in West Java are third highest in Indonesia and hasn’t reached the government target. Williamson Index of West Java always revolve around 0,64 every year, meaning high category nequality. West Java is the largest of center industrial areas in Indonesia, but industrial development aren’t evenly distributed and concentrated in the industrial areas. it can excacerbate development inequality between region. This study aims to analyze the development inequality, regional classification, and the influence of industry, agruculture, and human resources on development inequality in West Java. The methods include Klassen Typology analysis and panel data regression. The results shows large development inequality between region in West Java, changing classification in five region, and number of industri, industrial GRDP, and agriculture GRDP have positive effect on Bonet Index, number of industrial labor, RLS, and AHH have negative effect on Bonet Index.